2019
DOI: 10.33899/ijvs.2019.163192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Parascaris equorum in native horses in West Bank Palestine

Abstract: A total number of 435 fecal samples from native horses, aged between 6 months to 10 years of both sexes, were collected from eight cities at West Bank, Palestine during January 2015 to January 2017. The Mc Master egg counting and sedimentation methods were used for the detection of Parascaris equorum eggs in the collected samples. The overall prevalence rate of Parascaris equorum was found to be 15.6% (68 out of 435), and this rate varied significantly depending on the city. The highest prevalence rate was in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
2
2
1
Order By: Relevance
“…In line with previous studies, no significant differences were found between the prevalence rates, EPG means and MI between sexes [ 37 , 50 – 52 ]. The vast majority of positive animals in this study consisted of young horses managed in a uniform manner, independently of their respective sex (fillies or colts).…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies, no significant differences were found between the prevalence rates, EPG means and MI between sexes [ 37 , 50 – 52 ]. The vast majority of positive animals in this study consisted of young horses managed in a uniform manner, independently of their respective sex (fillies or colts).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study were in accordance with other studies in different areas; In India, the prevalence of Parascaris equorum in horses was higher in females (60.97%), compared to males (58.51%, Yadav et al, 2014). In Palestine, the prevalence rate was 15% in males and 16.5% in female horses (Singh et al, 2012;Othman and Alzuheir, 2019). There is no significant difference in prevalence rates between male and female horses in seven provinces of southern Poland which can be caused by the way of rearing, nutrition, and maintenance management (p > 0.05, Kornas et al, 2010).…”
Section: Resultssupporting
confidence: 91%
“…As can be seen in Table 2, the prevalence rate of Parascaris equorum infection differed significantly in male and female horses in Payakumbuh city (p < 0.05). Sex had a significant (p < 0.05) effect on the prevalence of Parascaris equorum in horses which was different from that report of Othman and Alzuheir who conducted a study in West Bank Palestine and with the result that there was no significant difference in the prevalence rate of Parascaris equorum between male and female (Othman and Alzuheir 2019). The results of this study were in accordance with other studies in different areas; In India, the prevalence of Parascaris equorum in horses was higher in females (60.97%), compared to males (58.51%, Yadav et al, 2014).…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations